Camera-based visual feedback learning aid for recovering sense of smell and taste in COVID-19 survivors: a proof-of-concept study - Kumari, Veena; Chauhan, Satyam; Vakani, Krupa; Antonova, Elena; Bryant, Jacky (Frontiers in Psychology, 2023)
A significant proportion of people report persistent COVID-19-related anosmia, hyposmia or parosmia, often accompanied with ageusia, hypogeusia or dysgeusia. Here, we present a proofof-concept study that assessed the feasibility and acceptability of a new Camera-Based Visual Feedback Learning Aid (CVFLA) and explored its potential to restore or improve persistent COVID-19-related smell and/or taste impairment. Fifteen adult participants with persistent smell and/or taste impairment were randomly allocated to 7-, 14-or 21-days baseline of symptom monitoring before receiving the intervention in up to 10 sessions (length and frequency determined by participant's preference and progress) using a specialised CVFLA apparatus (patent no. 10186160). Smell and taste were assessed pre-and post-intervention subjectively, and also objectively using the ODOFIN Taste Strips and Sniffin Sticks.Participant feedback about their experience of receiving CVFLA was obtained via a semistructured interview conducted by someone not involved in delivering the intervention. The intervention was extremely well received, with no drop-outs related to the intervention. There was also a significant improvement in smell and taste from pre-to post-CVFLA intervention (mean number of sessions=7.46, SD=2.55; total duration=389.96 min, SD=150.93) both in subjective and objective measures. All participants, except one, reported experiencing some improvement from the 2 nd or 3 rd session. This new CVFLA intervention shows promise in improving COVID-19 related impairment in smell and taste with a very high level of acceptability. Further studies with larger samples are required to confirm its potential in restoring, improving or correcting smell and/or taste impairment in relevant clinical and nonclinical groups.